2013
DOI: 10.1155/2013/364750
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Estimation of Ibuprofen and Phenylephrine Hydrochloride in Bulk and Combined Dosage Form by First Derivative UV Spectrophotometry Method

Abstract: A simple, precise, rapid, and economic method was developed for the simultaneous determination of Ibuprofen and Phenylephrine HCl in bulk and combined dosage form. This method involves first-order derivative spectroscopy using 248 nm and 237 nm as zero crossing points for Ibuprofen and Phenylephrine HCl, respectively. For spectrophotometric method 0.1 N NaOH was used as a solvent. The linearity was established over the concentration range of 12–72 μg/mL and 1.5–22 μg/mL for Ibuprofen and Phenylephrine HCl with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…The results show that the proposed method is 3–24 times more sensitive than the reported chromatographic methods for the simultaneous determination of NEB and AML. Moreover, the proposed method is 2–9 times more sensitive than the reported spectrophotometric methods for NEB and AML, respectively. This high sensitivity makes the proposed method superior to the chromatographic and spectrophotometric methods reported in the literature.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The results show that the proposed method is 3–24 times more sensitive than the reported chromatographic methods for the simultaneous determination of NEB and AML. Moreover, the proposed method is 2–9 times more sensitive than the reported spectrophotometric methods for NEB and AML, respectively. This high sensitivity makes the proposed method superior to the chromatographic and spectrophotometric methods reported in the literature.…”
Section: Resultsmentioning
confidence: 88%
“…A literature survey revealed that several of the analytical methods published for the determination of a combination of NEB and AML rely on the use of spectrophotometry , HPLC and HPTLC .…”
Section: Introductionmentioning
confidence: 99%
“…Scienti c reports showed several methods for assay of IBU 10 and PHE 11 in pharmaceuticals using different techniques for their simultaneous determination in different mixtures. Literature survey revealed few techniques for assaying IBU and PHE in their binary combination simultaneously such as spectrophotometry 12 , spectro uorimetry 13 and HPLC 14 . The two drugs were subjected to stability studies in their mixtures with other drugs 11d, 15 , but no method was developed for the stability indicating assay of this binary mixture.…”
Section: Ibuprofen (Ibu) (2rs)-2-[4-(2-methylpropylmentioning
confidence: 99%
“…Alternatively, the corresponding regression equations were derived. The results obtained were compared with those obtained by comparison methods (31)(32)(33).…”
Section: Standard Solutionsmentioning
confidence: 99%